Image encryption algorithm using dynamic permutation and large chaotic S-box - Qobbi, Younes; Jarjar, Abdellatif; Essaid, Mohamed; Benazzi, Abdelhamid (Multimedia tools and applications, 2023)
In this paper, a new image encryption algorithm is proposed by using the chaotic maps. This cryptosystem is used to encrypt the color images of any size using a dynamic permutation and a large substitution table. The permutation is used to perform the first phase of the encryption process. This permutation is generated by using three parameters calculated from the pixel’s values of three color channels (Red, Green and Blue) of the plaintext image. The second phase consists to make a substitution of the pixels of each channel using a large substitution table generated by three chaotic permutations, chaotic control vector and chaotic rotation vector. In order to increase the avalanche effect of our system, an enhanced cipher block chaining ECBC is used. The results obtained after several simulations carried out by our algorithm on images of different sizes, prove the security of our algorithm against statistical, brutal and differential attacks.